ANALYSIS OF THE SERVICE QUALITY OF SIMAS BAIK (ELECTRONIC-BASED MAIL MANAGEMENT SYSTEM) IN THE GOVERNMENT AND REGIONAL AUTONOMY BUREAU OF THE REGIONAL SECRETARIAT OF EAST JAVA PROVINCE - Salsabilla Salwa Aniendyta Putri (Universitas Negeri Surabaya, 2025)
The SIMAS BAIK application is one example of the implementation of e-Gov used by the Regional Secretariat of East Java Province. The purpose of this study is to describe the quality of SIMAS BAIK services at the Bureau of Government and Regional Autonomy of the Regional Secretariat of East Java Province. This study uses the theory of Ribbink et al, which has 5 dimensions, namely ease of use, supporting facilities (e-scape/web design), customization, responsiveness, and assurance. This study uses a qualitative method with a descriptive approach. Data collection techniques include interviews, observations and documentation. The results of the study indicate that the quality of SIMAS BAIK services at the Regional Secretariat of East Java Province is quite good. This can be seen from the ease of use dimension of increasing the number of SIMAS BAIK operators, the supporting facilities dimension (e-scape/web design) participating in socialization activities, the customization dimension of employee readiness to follow the digitalization era, responsiveness reporting complaints in accordance with the SOP, the assurance dimension of admins and operators are required to maintain data security. Suggestions given by researchers are: 1) Ease of Use adding several employees who will act as SIMAS BAIK operators or admins, 2) Supporting Facilities (E-Scape/Web Design) admins or operators who experience complaints immediately report in accordance with the SOP, 3) Customization admins and operators are required to participate in socialization activities in order to know and understand how to use the SIMAS BAIK application if there are additional features, 4) Responsiveness service officers apply a friendly attitude to service users, 5) Assurance operators or admins diligently back up letters to anticipate system errors or viruses.